PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP RETURN SAHAM PADA PERUSAHAAN PT KALBE FARMA TBK PERIODE 2013-2022 - Sofia, Farha; Sulistyani, Tri (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of profitability and leverage on stock returns in pharmaceutical and health companies PT. Kalbe Farma Tbk. for the period 2013-2022. Type of quantitative research using descriptive analysis and associative analysis techniques. The population and sample used in this research were all financial reports at PT. Kalbe Farma Tbk. The results of this research show that partially profitability has a positive and significant effect on stock returns, this can be seen from the ROE test results which show a value (tcount 2.945 > ttable 2.365) and a significant value (0.022 <0.05.) The results of the Leverage research show that partially negative and significant effect on stock returns. DER test results show that the value is (tcount -3.021 > ttable 2.365) and the value is significant (0.019 < 0.05). The results of the F test show that profitability and leverage simultaneously influence stock returns. This can be seen from the results of the F test which shows that the value (Fcount 4.930 > Ftable 4.460) and the significant result is (0.046 <0.05),with a coefficient of determination value of 0.867, which means that the profitability of leveraged funds has an effect of 86,7% on stock returns, while the remainder is 13,3% is influenced by other variables.